RELATIONSHIP BETWEEN READING HABITS AND READING COMPREHENSION ABILITY IN FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Nurjanah, Nurjanah; Djuanda, Dadan; Iswara, Prana Dwija (UNIKU PRESS, 2024)
This research is motivated by the low literacy scores of Indonesia according to the 2022 PISA, ranking 68 out of 81 countries, as well as the indication of low reading habits which consequently lead to difficulties in reading comprehension abilities. The aim of this research is to determine the relationship between reading habits and reading comprehension abilities among students. This study adopts a quantitative approach with a correlational method to identify the relationship between the variables under investigation. The research instruments used include interview guidelines, reading habits questionnaires, and Indonesian language tests. The results of this study indicate that (1) students' reading habits vary, some have high and moderate reading habits; (2) the level of students' reading comprehension abilities also varies, ranging from literal, reorganization, inferential, evaluative to appreciative levels, and there are those with low, moderate, and high reading comprehension abilities; (3) the significance value of 0.496 indicates a low significant relationship between reading habits and reading comprehension abilities among students. This low relationship suggests that further research on the relationship between reading determinant variables needs to be explored, for instance, for potential artificial intelligence development.Keywords: Reading Habits; Reading Comprehension Ability; Students